Final quality of life and safety data for patients with metastatic castration‐resistant prostate cancer treated with cabazitaxel in the UK Early Access Programme (EAP) (NCT01254279). (16th June 2015) - Bahl, Amit; Masson, Susan; Malik, Zafar; Birtle, Alison J.; Sundar, Santhanam; Jones, Rob J.; James, Nicholas D.; Mason, Malcolm D.; Kumar, Satish; Bottomley, David; Lydon, Anna; Chowdhury, Simon; et al.
Abstract : Objective: To compile the safety profile and quality of life (QoL) data for patients with metastatic castration‐resistant prostate cancer (mCRPC) treated with cabazitaxel in the UK Early Access Programme (UK EAP). Patients and Methods: A total of 112 patients participated at 12 UK cancer centres. All had mCRPC with disease progression during or after docetaxel. Patients received cabazitaxel 25 mg/m 2 every 3 weeks with prednisolone 10 mg daily for up to 10 cycles. Safety assessments were performed before each cycle and QoL was recorded at alternate cycles using the EQ‐5D‐3L questionnaire and visual analogue scale (VAS). Thes afety profile was compiled after completion of the UK EAP and QoL measures were analysed to record trends. No formal statistical analysis was carried out. Results: The incidences of neutropenic sepsis (6.3%), grade 3 and 4 diarrhoea (4.5%) and grade 3 and 4 cardiac toxicity (0%) were low. Neutropenic sepsis episodes, though low, occurred only in patients who did not receive prophylactic granulocyte‐colony stimulating factor. There were trends towards improved VAS and EQ‐5D‐3L pain scores during treatment. Conclusions: The UK EAP experience indicates that cabazitaxel might improve QoL in mCRPC and represents an advance and a useful addition to the armamentarium of treatment for patients whose disease has progressed during or after docetaxel. In view of the potential toxicity, careful patient selection is important.